2021
DOI: 10.1177/10775463211048256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of axial force on the stability of milling: Local bifurcations around stable islands

Abstract: In this paper, the stability properties of milling processes are presented when the axial component of the cutting force is also taken into account as a compressive force acting on the cutting tool. The mechanism of the material removal operation is described by a one degree-of-freedom oscillator subjected to the so-called surface regeneration effect. This can be represented mathematically by a nonlinear, time-periodic, delay differential equation. The regenerative compression affects the natural frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…It may lead to the Fig. 5 Percentage of the signal types processed in chatter detection literature omission of bistable zones, which are stable zones where a sizeable perturbance can still cause chatter [279,280]. The stability islands as shown in Fig.…”
Section: Stability Diagram and Chatter Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may lead to the Fig. 5 Percentage of the signal types processed in chatter detection literature omission of bistable zones, which are stable zones where a sizeable perturbance can still cause chatter [279,280]. The stability islands as shown in Fig.…”
Section: Stability Diagram and Chatter Predictionmentioning
confidence: 99%
“…7 are isolated zones in the SLD where the chatter condition shifts back and forth, and it is associated with the time periodicity. They are mostly dependent on the number of teeth, radial depth and the tool geometry [3,265,[280][281][282][283][284][285] and may occur even with multivariable cutters [286][287][288]. However, it is noted that when using FRF measurements for the calculation of the stability lobes, the results by Otto et al [289] showed that no stable or unstable islands were found because the probability for stability islands decrease for an increasing number of flexible eigenmodes.…”
Section: Stability Diagram and Chatter Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…These systems can be characterized by delay differential equations. Similar engineering problems involving time delay occur in balancing (Xu et al, 2016; Balogh et al, 2022), vehicle dynamics (Beregi et al, 2016), and machining processes (Beri and Stepan, 2021) as well, resulting in machine tool chatter. In recent years, various new methods have been developed to analyze delayed systems (Insperger et al, 2008; Liu and Kalmár-Nagy, 2010).…”
Section: Introductionmentioning
confidence: 99%